Clinical Studies on the Relation between Nonspecific Immunological Parameters and Pre-and Post-operative Immunological Activity in Colorectal Cancer Patients - Yanagita, K.; Nagasawa, N.; Yasushi, T.; Yoshio, T.; Kuwabara, T.; Honda, R.; Kobayashi, K.; Watanabe, M. (Nippon Daicho Komonbyo Gakkai Zasshi, 1988)
Peripheral blood lymphocytes, T cell subsets (percentages of OKT 3 cells, OKT4 cells, OKT 8 cells and IgG-Fc receptor positive T (FcR(+)T) cells), OKT 4/OKT 8 ratio, PHA and Con A-induced lymphoblastogenesis (stimulation index) and PPD skin test were examined at the pre-and post-operative stage (PO 2W, 1M, 3M, 6M) in 51 colorectal cancer patients and were analyzed according to the various stages of cancer. On the basis of correlations among these parameters, pre-and post-operative nonspecific immunological activity was discussed. In the pre-operative period in more advanced cases, increase of OKT 8 and reduction of OKT 4/OKT 8 ratio, PHA and Con A-induced lymphoblastogenesis and PPD skin test were observed in comparison with the other cases. In patients given curative resection for rectal cancer, decrease of lymphocytes and reduction of PHA and Con A-induced lymphoblastogenesis and PPD skin test were observed at PO 2 W, and these recovered 3 M later. On the other hand, in patients with non curative resection, these parameters were reduced at PO 3 M and 6 M. It is suggested from these results that the above parameters are useful for the assessment of immunological activity in colorectal cancer patients.